1977
DOI: 10.1128/jb.129.3.1623-1627.1977
|View full text |Cite
|
Sign up to set email alerts
|

Altered outer membrane protein in different colonial types of Neisseria gonorrhoeae

Abstract: Dark-colored colony types of Neisseria gonorrhoeae (T3 and dark variants of T1 and T2) had markedly increased amounts of an approximately 28,000-dalton outer membrane protein, as compared with light-colored colony types (T4 and light variants of T1 and T2). The presence of this protein appeared to be unrelated to piliation. The apparent molecular weight of this protein on sodium dodecyl sulfate-polyacrylamide gels varied, depending on methods used to solubilize envelope proteins. In view of the location of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
1

Year Published

1978
1978
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 16 publications
2
38
1
Order By: Relevance
“…We have found that the use of 2% Sarkosyl to selectively remove cytoplasmic membrane proteins from total membrane preparations ofNeisseria genorrhoeae provides a rapid and reproducible method for extracting outer membrane proteins. The protein profile seen after SDS-polyacrylamide gel electrophoresis, as has been noted before [11 ], is directly comparable with that obtained by other methods [11][12][13].…”
Section: Extraction Of Outer Membrane Proteinssupporting
confidence: 85%
See 1 more Smart Citation
“…We have found that the use of 2% Sarkosyl to selectively remove cytoplasmic membrane proteins from total membrane preparations ofNeisseria genorrhoeae provides a rapid and reproducible method for extracting outer membrane proteins. The protein profile seen after SDS-polyacrylamide gel electrophoresis, as has been noted before [11 ], is directly comparable with that obtained by other methods [11][12][13].…”
Section: Extraction Of Outer Membrane Proteinssupporting
confidence: 85%
“…The variations in the proteins induced in the different strains is one further example of the considerable heterogeneity in the protein composition of the gonococcal outer membrane. Previous observations have noted differences in the molecular weight of the major outer membrane protein [17], and also in several proteins with molecular weights between 25 000 and 30 000, which affect colony colour [11,14]. This is, to our knowledge, the first demonstration that it is possible to regulate, in vitro, the protein composition of the outer membrane of Neisseria gonorrhoeae.…”
Section: Discussionsupporting
confidence: 52%
“…These findings are of interest, since Walstad et al (13) and Swanson (12) have shown that GC organisms from opaque T2 colonies of isogenic strains contain extra proteins as demonstrated by polyacrylamide gel electrophoresis of outer membrane preparations. They do not seem to be associated with pili, since they were absent in pilated transparent colonies of the isogenic strain.…”
Section: Discussionmentioning
confidence: 89%
“…no. 348) and Walstad et al in a study of cell envelope proteins (28). Because (middle column) colony type 3 gonococci isolated from the cervix and urethra of heterosexual partners (note difference in height of one peak in section VI); (right column) colony type 2 gonococci isolated from the cervix and urethra ofheterosexual partners.…”
Section: Discussionmentioning
confidence: 99%
“…Since agreement was present in the latter two tests, we did not suspect dual infections with different gonococci. Walstad et al have shown that different electrophoresis patterns may be present in cell envelope proteins of the same colony type of a single isolate (28). The difference depended on whether the colony type was dark or light colored.…”
Section: Discussionmentioning
confidence: 99%